PENGARUH PROMOSI, LOKASI DAN CITRA MEREK TERHADAP KEPUTUSAN MENGINAP PADA KAMPUNG GAJAH MAS VILA BATURITI - Ni Made Apta Nariswari; Daniel Manek (Jurnal Bakti Saraswati (JBS), 2024)
The purchase decision or stay decision is a series of performance in the form of a process of selecting alternatives that involves efforts to determine the choice of product or service to be purchased. Factors that can influence the decision to stay are promotions, location and brand image. The aim of this research is to determine the influence of promotion, location and brand image on the decision to stay at Kampung Gajah Mas Vila. The population in this study were all customers who came and stayed at Kampung Gajah Mas Baturiti Tabanan, Bali. The number of samples used in this research was 90 consumers as respondents. Data were collected by distributing questionnaires using a Likert scale with a score of 1 to 5. The data analysis technique used multiple linear regression analysis. The research results show that promotion has a positive and significant effect on the decision to stay at Kampung Gajah Mas Vila Baturiti. Location has a positive and significant influence on the decision to stay at Kampung Gajah Mas Vila Baturiti. Brand image has a positive and significant influence on the decision to stay at Kampung Gajah Mas Vila Baturiti.